Perspektif Teologi Pembebasan dan Keadilan Sosial Terhadap Penderitaan Yesus di Salib - Denny Andreas; Sharon Evangelica (LPPM STT Baptis Kalvari, 2024)
This article discusses the meaning of the death of Jesus Christ on the cross in the context of liberation theology and social justice, focusing on the suffering experienced by Jesus in the cross narrative. The theological approach used integrates the perspectives of liberation theology and social justice in the Indonesian context, which enriches the understanding of Jesus' sacrifice for humanity. Through historical and theological analyses, this article outlines the process of torture and suffering experienced by Jesus before the crucifixion, as well as its implications in the context of social justice and liberation. By considering the Indonesian context, this article also explores how Jesus' suffering on the cross can provide inspiration for Christians in fighting for social justice and solidarity in society. Thus, this article contributes to the theological understanding of the suffering of Jesus Christ and its relevance in the contemporary Indonesian context